Screening adherence and cancer risk perceptions in colorectal cancer survivors with Lynch‐like syndrome. Issue 3 (14th September 2015) - Katz, L.H.; Burton‐Chase, A.M.; Advani, S.; Fellman, B.; Polivka, K.M.; Yuan, Y.; Lynch, P.M.; Peterson, S.K.
Abstract : Cancer screening recommendations for patients with Lynch‐like syndrome (LLS) are not well defined. We evaluated adherence to Lynch syndrome (LS) screening recommendations, cancer risk perceptions, and communication within the families among colorectal cancer (CRC) survivors with LLS. Thirty‐four participants with LLS completed a questionnaire about risk perception, adherence to LS screening recommendations, and communication with relatives. Clinical data were obtained from medical records. Most participants (76%) believed they should undergo colonoscopy every 1–2 years. Only 41% correctly interpreted their genetic tests as uninformative negative or as variant of unknown significance for LS. Less than half had had an upper gastrointestinal endoscopy for screening purpose. Among female participants, 86% had been screened for endometrial cancer (EC) and 71% for ovarian cancer. Most participants had informed relatives about the CRC diagnosis and advised them to undergo CRC screening, but only 50% advised female relatives to be screened for EC and only one‐third advised relatives to have genetic counseling. Most CRC survivors with LLS follow the same cancer screening recommended for LS patients but do not understand the meaning of LLS. Greater care must be devoted to communicating the implications of nondiagnostic germline mutation testing among patients with LLS. Abstract : Section Editor: Aad Tibben, email:a.tibben@lumc.nl